1998
DOI: 10.1074/jbc.273.38.24832
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interleukin-1β-induced Interleukin-6 Gene Expression in Human Fibroblast-like Synoviocytes by p38 Mitogen-activated Protein Kinase

Abstract: Involvement of p38 mitogen-activated protein (MAP) kinase in interleukin (IL)-6 gene expression of human fibroblast-like synoviocytes (FLSs) was assessed. p38 MAP kinase was constitutively expressed in human FLSs and activated in response to IL-1␤. A pyridinylimidazole compound, SB203580, inhibited p38 MAP kinase activity in vivo, since the activity of MAPKAP kinase-2 (a substrate of p38 MAP kinase) in IL-1␤-stimulated FLSs was totally suppressed by it. SB203580 concentrationdependently inhibited protein produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 60 publications
9
149
2
1
Order By: Relevance
“…There are several other reports that suggest the relevance of MAPK activation to the immunopathogenesis of RA (48)(49)(50)(51)(52). However, no report has described the effects of MAPK pathway inhibitors on the ex vivo cytokine production by freshly isolated synovial cells from RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other reports that suggest the relevance of MAPK activation to the immunopathogenesis of RA (48)(49)(50)(51)(52). However, no report has described the effects of MAPK pathway inhibitors on the ex vivo cytokine production by freshly isolated synovial cells from RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the signaling pathways responsible for IL-6 mRNA stabilization. It has been found by multiple groups that the mitogen-activated protein kinase (MAPK) p38 stabilizes IL-6 mRNA [12,[15][16][17][18]. Another kinase often associated with mRNA stabilization is protein kinase C (PKC).…”
Section: Page 4 Of 48mentioning
confidence: 99%
“…It has been shown that IL-1β stabilizes multiple mRNA species, including IL-6, in a variety of cell types [9,12,14,16,35,36]. A paradigm commonly used to study effects on mRNA stabilization is the blockade of new transcription by a transcriptional inhibitor, such as actinomycin D, followed by quantification of the mRNA levels at several time points after inhibition of transcription [37].…”
Section: Il-1β Stabilizes Il-6 Mrnamentioning
confidence: 99%
See 2 more Smart Citations